Effects of Augmented Reality Interventions on the Function of Upper Extremity and Balance in Children With Spastic Hemiplegic Cerebral Palsy: A Randomized Clinical Trial - Malick, Wardah Hussain; Butt, Rizwana; Awan, Waqar Ahmed; Ashfaq, Muhammad; Mahmood, Qamar (Frontiers in Neurology, 2022)
Objective: To determine the effects of augmented reality (AR) interventions on the function of the upper extremity (UE) and balance in children with spastic hemiplegic cerebral palsy (SHCP). Methods: Thirty children with SHCP, aged 6 to 12 years, were randomly divided into three interventional groups. Each group received an AR game i.e., Balance It, Bubble Pop, or Scoop’d (WonderTree, Pakistan). The UE function and balance were assessed at the baseline and after eight weeks of intervention through the Disability of Arm, Shoulder, and Hand (DASH) questionnaire and Pediatric Balance Scale (PBS) respectively. Paired sample t-test and Wilcoxon signed-rank test was used for analyzing the changes in the total DASH and PBS scores within the groups respectively. One-way ANOVA was used to determine the differences between the groups in the total DASH and PBS scores, while the Kruskal Wallis test was used for the differences between the groups in the PBS items. The data were analyzed by using SPSS version 21. Results: All the groups improved significantly in the total DASH and PBS scores post-intervention. A significant difference was determined in standing with one foot in front between Bubble Pop and Scoop’d groups. The total score of PBS also showed a significant difference between Bubble Pop and Balance It groups. Conclusion: The AR interventions used in this study were found to be effective in improving the UE function and balance of children with SHCP. The Balance It game showed more promising results in improving the balance as compared to the other games, however, no significant difference was determined between the three AR games in terms of the UE function of the participants.